The NLP anchoring technique compared to person-centered counseling and rational-emotive therapy in enhancing self-esteem - Nellikunnel, Joseph (Animo Repository, 1992)
This study determines the effectiveness of Neuro-Linguistic Programming (NLP) Anchoring in comparison to Person-Centered Counseling (PCC) and Rational-Motive Therapy (RET) in enhancing self-esteem. A modification of Campbell's randomised pretest-posttest experimental design was employed in this study. The subjects were 45 female third year high school students, who were randomly assigned to the three treatment modes. Instruments used were Tennessee Self-Concept Scale (TSCS), Draw a Person (DAP) Test, Behavior rating scale and counselee feedback. Data were subjected to a two-way repeated measures design, which is a type of analysis of variance (ANOVA), and an analysis of covariance (ANCOVA). Differences between means were computed and compared using the Least Significant Difference (LSD) at .05 level. The NLP Anchoring group had only one treatment session while the other two groups had three counseling sessions each. At the end of the first session, the NLP Anchoring group had a significantly higher score of self-esteem than its pretest score, p.01, as measured by TSCS, while the other two groups did not have a significantly higher posttest score. Furthermore, the posttest score of NLP Anchoring group was significantly higher than that of the PCC and RET groups, p.01. The groups counseled by PCC, RET and NLP Anchoring, at the end of 3 sessions, had significantly higher scores of self-esteem than their corresponding pretest scores, p.01 as measured by TSCS. DAP posttest scores did not show significant improvement.